From Participation to Performance: The impact arts management can have on an inclusive community choir’s identity - Gibson, Sarah-Jane (Irish Journal of Arts Management and Cultural Policy, 2019)
Through a case study of the Open Arts community choir’s engagement in a televised talent show, this research article explores the complex influences of managers such as TV producers on the performance and misrepresentation of inclusive choirs. It is widely acknowledged that choral singing can provide a rewarding experience for participants. However, an important aspect to choral practice is performing to an audience, who may have preconceived impressions of the choir. This can influence the manner in which marginalised choral singers perceive themselves. The findings in this article are based on ethnographic research with the Open Arts community choir from Belfast, which comprises some members with disabilities. The research draws upon ‘communities of practice’ (Wenger, 1998) and the performance theories of academics such as Victor Turner (1969). I demonstrate the complexity of the interactions that occur between the choir and the producers of two television shows, and also how the singers sometimes expressed that there were discrepancies between their perceptions of the choir and the manner in which they were presented by the shows’ producers. At times, this difference between perception and representation caused members to feel misrepresented and unable to enjoy performing. As a result, the aim of the article is to consider how those in arts management can better support inclusive musical groups in effectively presenting their desired image to audiences.